Proposal to conceive multimedia systems from a value creation perspective and a collaborative work routes Approach (2021)
Methodologies for the development of interactive multimedia systems traditionally apply the practices and lifecycles of user-centred design in conjunction with usability and accessibility practices guided by software engineering process models. This work contributes to the conception of multimedia systems through a new way of working using a set of work routes encouraging collaborative work. This new approach to conceive multimedia systems is centred on value creation and value-sensitive design, through a formal characterisation based on theoretical foundations. The results obtained from an evaluation of this definition, using a case study in an academic context, show that our scheme facilitates the conception and planning of factors such as the interactive multimedia experience and the responsible design of the solution